Development of Emulsions Containing L-Ascorbic Acid and α-Tocopherol Based on the Polysaccharide FucoPol: Stability Evaluation and Rheological and Texture Assessment - Sílvia Baptista; Filipa Baptista; Filomena Freitas (Cosmetics, 2023)
The main function of vitamin C, as an antioxidant, is to combat free radicals and prevent premature aging, smoothing wrinkles and expression lines. In addition, it acts directly on depigmentation and prevention of blemishes on the skin. In this study, natural oils (30 wt.%) and α-tocopherol (2.5 wt.%) containing oil-in-water (O/W) emulsions stabilized with the bacterial fucose-rich polysaccharide FucoPol were formulated, adding L-ascorbic acid as an antioxidant. The optimized formulations were obtained with 8.0 wt.% L-ascorbic acid for the Olea europaea oil formulation (C1) with a ƞ value of 2.71 Pa.s (measured at shear rate of 2.3 s−1) and E24 = 96% and with 15 wt.% L-ascorbic acid for the Prunus amygdalus dulcis formulation (C2) with a ƞ value of 5.15 Pa.s (at a shear rate of 2.3 s−1) and E24 = 99%. The stability of the FucoPol-based formulations was investigated over 45 days at 4 °C, 20 °C, and 30 °C. The results showed that all formulations maintained the organoleptic characteristics, with pH variations (5.7–6.8 for C1, and 5.5–6.03 for C2) within the regulations for cosmetic products (4 ≤ pH ≤ 7). The accelerated stability tests proved the formulations’ stability at 4 °C with EI = 95% for C1 and EI = 100% for C2. The rheological assessment demonstrated that the formulation presents a shear-thinning and liquid-like behavior. Regarding textural parameters, formulations C1 and C2 displayed an increase in firmness and consistency with similar spreadability during the shelf life. These findings further demonstrate FucoPol’s functional properties, acting as an emulsifier and stabilizer polysaccharide in cosmetic formulations containing L-ascorbic acid.